Composition of the Board of Directors and the Likelihood of Disclosure of Social Responsibility Reports - Aparecida Silva Jacques, Kelly; Lemes, Sirlei; Lopes Fávero, Luiz Paulo; Portela de Lima Rodrigues, Lúcia Maria (Review of Business Management, 2023)
Purpose – To identify the relationship between characteristics of the Board of Directors and the dissemination probability of socially responsible reports. Theoretical framework – Considering the central role of the Board of Directors in mitigating conflicts of interest, the study is based on the Stakeholders-Agency Theory. Design/methodology/approach – The sample included 250 companies listed on the Brazilian stock exchange (B3). The data used were collected in the “Relate or Explain” Report, Economática® and CVM Reference Form, and then operationalized using a binary logistic regression model. Findings – The results suggest that the dissemination chance of socially responsible reports is 1.52% higher in companies with more concentrated shares, 101.10% higher in larger companies and 59.2% lower in companies with dual positions. Research Practical & Social implications – The findings can be useful to (i) direct organizational strategies for the composition of the Board of Directors that improve the dissemination of socially responsible reporting, (ii) to foster discussions about changes in the classification of levels about corporate governance at B3 and (iii) decision-making by several stakeholders. Originality/value – To the Accounting Academy, the study promotes an additional debate on the role of the Board of Directors in dealing with the Agency Theory. The study innovates by showing how the characteristics of the Board of Directors can change the potential for dissemination of socially responsible reports. Keywords – Stakeholder‐agency theory.; Corporate social responsibility; Corporate governance.